Representations of the weighted WG inverse and a rank equation's solution - Ferreyra, David Eduardo (2022)
In this paper, we present several representations of the W-weighted WG inverse. These representations are expressed in terms of matrix powers as well as in terms of matrix products involving only the Moore–Penrose inverse. In addition, a new characterization of the W-weighted WG inverse is presented by using a rank equation.